The selection process of biomass materials for the production of bio-fuels and co-firing - Altawell, Najib (Hoboken, New Jersey : IEEE/Wiley, 2014)
"Beginning first with the fundamentals of biofuel and co-firing, this essential resource then moves into coverage of the methodology that assists energy scientists and engineers to arrive at optimal biomass materials that are tailored to each company's business and economic environments. Coverage provides vital, ample, accurate, and detailed data of a number of energy crops and their uses by scientists. The unique approach includes not only technical and scientific factors, but also business factors such as environmental and human health factors for using biofuel and co-firing"--
"This book provides in full detailed examination and analysis for a number of energy crops and their use as a source for generating electricity and for the production of biofuels"--
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Biomass chemicals; Renewable energy sources; TECHNOLOGY & ENGINEERING / Agriculture / Sustainable Agriculture; Biomass chemicals; Renewable energy sources; Electronic books; Electronic books